Pakistani-American Muslim women identity negotiation as reflected in diaspora literature - Asiyah, Nur (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2020)
Identity is significant issue in the world. Pakistani-American Muslim women faced the problems of identity because they got different treatment in the society. This study reveals how do Pakistani-American Muslim women negotiate their identity and the result of negotiation? This research was done under descriptive qualitative research. The data of the research are the words, phrases, and sentences from diasporic literature entitled Saffron Dreams by Shaila Abdullah that published in 2009. To analyze the data, this study used postcolonial theory based on Bhabha’s hybridity and Tomey’s identity negotiation concept. Based on the research, it is found that Pakistan American Muslim women negotiate their identity by mindful negotiation namely adapting American culture and shaping hybrid identity. They change their fashion style by putting off their veils. They replace Arabic name into American style to hide their religious identity. In building the house they American building with Arabian nuance. On the other hand, in assimilating the culture to get a job, Pakistani American Muslim women must fight harder because of the striking differences in culture and the idealism they believe in.